Conceptions about critical thinking in primary and secondary education. A literature review (Revista Innova Educación, 2023)
Introduction: critical thinking has become a fundamental notion of educational policies and discourses, to such an extent that its presence is unquestionable. However, its conception is multifaceted along with its training and evaluation practices. Objective: to analyze various conceptions of critical thinking in primary and secondary education, in order to determine its characteristics, its primordial features and the ways in which it is understood and formed. Methodology: a systematic review was carried out, considering 60 investigations published worldwide between 2017 and 2022, in the Scopus and Dimensions databases, using eligibility criteria whose central search category was critical thinking in relation to primary and secondary education. Results: an education based on critical thinking has a positive impact on school interactions and on student training processes; In addition, the possibility of integrating the conceptions of critical thinking can favor educational processes. Conclusion: the heterogeneous conceptions of critical thinking in primary and secondary education can contribute to its understanding and training and evaluation practices, when thought in situated terms. Training in critical thinking is cardinal today, especially because of its importance in education for the twenty-first century and its possibility to develop both ways of thinking and autonomous, critical and ethical behaviors.
Keywords: conceptions; critical thinking; primary education; secondary education; training